Comparative Expression of Renin-Angiotensin Pathway Proteins in Visceral Versus Subcutaneous Fat - Zhang, Yuebo; Somers, Kiran R.; Becari, Christiane; Polonis, Katarzyna; Pfeifer, Michaela A.; Allen, Alina M.; Kellogg, Todd A.; Covassin, Naima; Singh, Prachi (Frontiers in Physiology, 2018)
Body fat distribution contributes to obesity-related metabolic and cardiovascular disorders. Visceral fat is more detrimental than subcutaneous fat. However, the mechanisms underlying visceral fat-mediated cardiometabolic dysregulation are not completely understood. Localized increases in expression of the renin angiotensin system (RAS) in adipose tissue (AT) may be implicated. We therefore investigated mRNA and protein expression of RAS components in visceral versus subcutaneous AT using paired samples from individuals undergoing surgery (N=20, body mass index: 45.6 ± 6.2 kg/m2, age: 44.6 ± 9.1 years). We also examined RAS-related proteins in adipose tissue obtained from individuals on renin angiotensin aldosterone system (RAAS) targeted drugs (N=10, body mass index: 47.2 ± 9.3 kg/m2, age: 53.3 ± 10.1 years). Comparison of protein expression between subcutaneous and visceral AT samples showed an increase in renin (p=0.004) and no change in angiotensinogen (p=0.987) expression in visceral AT. Among proteins involved in angiotensin peptide generation, angiotensin converting enzyme (p=0.02) was increased in subcutaneous AT while chymase (p=0.001) and angiotensin converting enzyme-2 (p=0.001) were elevated in visceral fat. Furthermore, visceral fat expression of angiotensin II type-2 receptor (p=0.007) and angiotensin II type-1 receptor (p=0.031) was higher, and MAS receptor (p<0.001) was lower. Phosphorylated-p53 (p=0.147), AT fibrosis (p=0.138) and average adipocyte size (p=0.846) were similar in the two depots. Nonetheless, visceral AT showed increased mRNA expression of inflammatory (TNFα, p<0.001; IL-6, p=0.001) and oxidative stress markers (NOX2, p=0.038; NOX4, p<0.001). Of note, mRNA and protein expression of RAS components did not differ between subjects taking or not taking RAAS related drugs. In summary, several RAS related proteins are differentially expressed in subcutaneous versus visceral AT. This differential expression may not alter AngII but likely increases Ang1-7 generation in visceral fat. These potential differences in active angiotensin peptides and receptor expression in the two depots suggest that localized RAS may not be involved in differences in visceral vs subcutaneous AT function in obese individuals. Our findings do not support a role for localized RAS differences in visceral fat-mediated development of cardiovascular and metabolic pathology.